Sentiment Analysis Based on Reviews Using Machine Learning Techniques - Ameema Sattar; Joddat Fatima (Pakistan Journal of Engineering & Technology, 2021)
In our daily life, people’s opinions and experiences are important sources of information. To measure the feeling of people’s opinions the term used that is called sentiment analysis. The text is the main method of communicating on the Internet in modern digital time. Sentiment analysis captures the user’s views, moods, and their opinion related to the specific services provided by the business organization in a real-time. This research focuses on Roman Urdu reviews. It has three basic classes: negative, positive, and neutral where reviews are classified. The proposed method is Analysis of different machine learning algorithms with different datasets has made and a comparison shows, SVM performs the best result on used data sets, a clear result in the form of accuracy, precision, recall, and f1 score shows the results against the specific techniques against the dataset.